Supporting offshore wind growth: Automating data analysis in digital aerial surveys to enhance wildlife protection and survey efficiency - Ben Bartlett; Matheus Santos; Petar Trslic; Gerard Dooly (Ecological Informatics)
With Europe projected to install 260 GW of new wind power between 2024 and 2030, much of it offshore, efficient Environmental Impact Assessments (EIAs) are essential. Regulations require 24 monthly aerial digital surveys before development, with continued monitoring during and after construction. This generates massive volumes of ecological data. We present an automated system that drastically reduces the time required for the most labour-intensive task: screening imagery to identify objects or individuals for further species classification. The process is reduced from several months to the 4-hour survey duration. In a 15-month case study (with one month excluded for testing), the system achieved 97.9 % accuracy, outperforming manual screening (68.75 %), and eliminated 99.13 % of frames from requiring manual review. Avian detection matched manual performance but remained limited by current survey conditions and image resolution. Critically, we found that the commonly assumed 2 cm ground sampling distance (GSD) was inconsistent across survey frames, with no part of any image achieving 2 cm/px, due to camera angles and aircraft configuration. This reduces classification confidence and highlights a need for improved data standards and transparency. As the first study to directly examine these assumptions using raw data, our results demonstrate that survey resolution is insufficient for consistent species identification, and that manual screening may miss up to 30 % of individuals. These findings underscore the importance of questioning inherited data assumptions and improving survey methodologies before such outputs are used to inform policy or conservation action.